cag+ Helicobacter pylori induces homotypic aggregation of macrophage-like cells by up-regulation and recruitment of intracellular adhesion molecule 1 to the cell surface. - Moese, S.; Selbach, M.; Meyer, Thomas F.; Backert, Steffen (Infection and Immunity, 2002)
Infection with cag+ but not cag-negative Helicobacter pylori leads to the formation of large homotypic aggregates of macrophage-like cells. Intracellular adhesion molecule 1 is up-regulated and recruited to the cell surface of infected cells and mediates the aggregation via lymphocyte function-associated molecule 1. This signaling may regulate cell-cell interactions and inflammatory responses.